Financial Sector Policy in Practice : Benchmarking Financial Sector Strategies around the World - Maimbo, Samuel Munzele; Melecky, Martin (World Bank, Washington, DC, 2014)
Policy makers use financial sector strategies to formulate a holistic policy for their national financial sectors. This paper examines and rates financial sector strategies around the world based on how well they formulate development targets, arrangements for systemic risk management, and implementation plans. The strategies are also rated on whether they consider policy trade-offs between financial development and systemic risk management. The rated strategies are then benchmarked against a wide range of country characteristics. The analysis finds that the scope and quality of national strategies for the financial sector are influenced by the country's type of legal system, its level of income and macroeconomic stability, the existing financial depth and inclusion, the share of foreign ownership in the national financial sector, and the experience of past financial crises. Giving due consideration to policy trade-offs, particularly between financial development and systemic risk management, remains the weakest part of these strategies. Countries with civil- and religious-based law and those with a higher share of foreign ownership in their financial system address the policy trade-offs more often.